Gender Differences in Anxiety and Its Relation to Academic Achievement - Khan, Aiyaz Ahmad; Samad, Abdul (THE PRIMARY TEACHER, 2022)
Anxiety is a major area of interest within the field of education. The present study aims to compare and measure the anxiety of boys and girls at the primary level, and to ascertain the association between academic achievement and anxiety of students at the primary level across gender. The sample consisted of 210 students of Class V from seven government schools of Murshidabad district, West Bengal. The data was collected using the Spence Children’s Anxiety Scale-Child (1998). Using statistical techniques including t-test, Pearson correlation and T-score, the collected data was analysed. The results of the present study revealed that girls at the primary level are more in number and percentage having elevated anxiety. Apart from obsessive compulsive disorder and physical injury fear, the study clearly shows that there were no gender differences in any anxiety subscales. The researchers identified a negative association between academic achievement and anxiety among primary students.